Early development of decision support systems based on artificial intelligence: an application to postoperative complications and a cross-specialty reporting guideline for early-stage clinical evaluation - Vasey, B (2023)
Background: Complications after major surgery occur in a similar manner internationally but the success of response process in preventing death varies widely depending on speed and appropriateness. Artificial intelligence (AI) offers new opportunities to provide support to the decision making of clinicians in this stressful situation when uncertainty is high. However, few AI systems have been robustly and successfully tested in real-world clinical settings. Whilst preparing to develop an AI decision support algorithm and planning to evaluate it in real-world settings, a lack of appropriate guidance on reporting early clinical evaluation of such systems was identified. Objectives: The objectives of this work were twofold: i) to develop a prototype of AI system to improve the management of postoperative complications; and ii) to understand expert consensus on reporting standards for early-stage evaluation of AI systems in live clinical settings. Methods: I conducted and thematically analysed interviews with clinicians to identify their main challenges and support needs when managing postoperative complications. I then systematically reviewed the literature on the impact of AI-based decision support systems on clinicians’ diagnostic performance. A model based on unsupervised clustering and providing prescription recommendations was developed, optimised, and tested on an internal hold out dataset. Finally, I conducted a Delphi process, to reach expert consensus on minimum reporting standards for the early-stage clinical evaluation of AI systems in live clinical settings. Results: 12 interviews were conducted with junior and senior clinicians identifying 54 themes about challenges, common errors, strategies, and support needs when managing postoperative complications. 37 studies were included in the systematic review, which found no robust evidence of a positive association between the use of AI decision support systems and improved clinician diagnostic performance. The developed algorithm showed no improvement in recall at position ten compared to a list of the most common prescriptions in the study population. When considering the prevalence of the individual prescriptions, the algorithm showed a 12% relative increase in performance compared to the same baseline. 151 experts participated in the Delphi study, representing 18 countries and 20 stakeholder groups. The final DECIDE-AI checklist comprises 27 items, accompanied by Explanation & Elaboration sections for each. Conclusion: The proposed algorithm offers a proof of concept for an AI system to improve the management of postoperative complications. However, it needs further development and evaluation before claiming clinical utility. The DECIDE-AI guideline provides a practicable checklist for researchers reporting on the implementation of AI decision support systems in clinical settings, and merits future iterative evaluation-update cycles in practice.